Muttaqin: Tujuan Akhir Pendidikan Manusia (Kajian Pedadogis) - Sri Mulyani; Syamsurizal Yazid (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This article discusses the significant emphasis Islam places on education. It is evident that Islam has specific goals and reasons regarding this matter. The article elaborates on Islam's purpose in encouraging its followers to pay attention to education. It references several Quranic verses related to the objectives of education, explaining them not by relying on a single tafsir (exegesis) but by consulting multiple interpretations. Additionally, it compiles hadiths related to the objectives of education. In writing this, the author also gathers opinions from Muslim scholars and several contemporary figures considered relevant to the goals of education.